(untitled) (Revista Venezolana de Salud Pública, 2020)
Oswaldo Valdivia MD was born in 1937 in Arequipa, Peru. He started his studies in medicine in 1958, the first year the love of neuroanatomy rose and the fourth year he started like teacher. He graduated as medical doctor in 1964 and as anatomical pathology in 1966. He married with Zulema Valdivia at 1962 and he had 3 children with her, he got a scholarship to train electronic microscopic at the Wisconsin University at 1968. He decided to migrate to Venezuela in 1973, it dues the situations of Peru and by an offer to work by the Centroccidental Lisandro Alvarado University (UCLA) where he worked as a full-time professor of microscopic anatomy, he made numerous contributions such as the incorporation of electronic microscopy in the central-western region of the country in 1980. He did multiple research; his main focus was leishmaniasis disease. He worked as an active retired teacher at the UCLA to the last day of life. In his professional practice he made a great contribution to public health, like cervical pathology research and training health professionals until he passed away at November 18th, 2019 in Peru.